Urban meltdown : cities, climate change and politics as usual - Doucet, Clive (New Society Publishers, 2007)
Urban Meltdown anchors climate change in cities where 80 percent of the greenhouse gases are generated. An insiders take on how city council really works, it calls for a radical change in how cities grow, are managed and are governed.